Pelatihan dan Komitmen Organisasi, Pengaruhnya Terhadap Kinerja Karyawan PDAM Lematang Enim Kabupaten Muara Enim - Arubina Bangsawan; Fatma Oktarendah; Tutik Pebrianti; Zein Ghozali (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of training and organizational commitment on employee performance at PDAM Lematang Enim. The research design uses the causality method with the Multiple Linear Regression data analysis technique. The object of research is the active employees of PDAM Lematang Enim Muara Enim Regency, which number as many as 124 people. The data collection method that the authors use in this study is a questionnaire, which is carried out technically through a Google Form (Online). The results of the research show that Training and Organizational Commitment have a Positive and Significant Effect on the Employee Performance of PDAM Lematang Enim. Furthermore, between the two independent variables in this study, the variable that has a more dominant influence on performance is employee training. Even though the influence of training is very dominant, in implementing it, employee training at PDAM Lematang Enim must be improved in order to continuously maximize performance.